THE METHODS OF TEACHING STORIES IN PRIMARY EDUCATION - Sobitova Mohinur; Mohinakhon Khamidova (Journals Park Publishing, 2022)
In this article, the methodology of reading in primary school is literary education. The need to work as a method of teaching literature in primary school will be taught as a preparatory subject for a systematic course, methodology to the content of literary education of the primary school teacher and his teaching able to approach independently, not only to study the experience of others, rather, they consciously analyze the results of their activities and draw the right conclusions. It is said that they know.
Keywords: literary education; literary analysis; interpretation